(untitled) (Research, Society and Development, 2020)
The use of silage from tropical forages is another alternative to minimize the shortage of forage in the dry season, among the forages that can be adopted, elephant grass deserves mention. In this context, the objective of the work was to evaluate the bromatological aspects and fermentative quality of elephant grass silage added with cupuaçu seed cake. The experiment design was a completely randomized with five treatments and four replications, named: SCE = 100% pure elephant grass silage; STC20 = silage 80% elephant grass + 20% cupuaçu cake; STC40 = silage 60% elephant grass + 40% cupuaçu seed cake; STC60 = silage 40% elephant grass + 60% cupuaçu seed cake and STC80 = silage 20% elephant grass + 80% cupuaçu seed cake. PVC silos with 50 cm in length, 10 cm in diameter and 3.5 kg capacity were used. After 60 days of fermentation, the silos were opened, weighed again, homogenized and samples were taken to determine the contents of: MS, PB, FDN , FDA, MM, EE, CEL, HEM, LIG, MM, PMS, PE, PG and silage pH. In terms of chemical composition, the STC80 silage was the one that presented the best results, in addition to decreasing DM losses, effluent and gas losses. Therefore, it is recommended to include 80% of the cupuaçu seed cake in the silage with elephant grass, as it improves the fermentative profile and the chemical composition of the silage. Key words: Conservation; Critical periods; Fodder; Pennisetum purpureum; Strategies.